The Effect of Google Sites-Based Physics Learning Media with Problem-Based Learning on Student Outcomes - Nurulwati, Nurulwati; Amelia, Faraz Rizky; Susanna, Susanna; Elisa, Elisa; Hamid, Abdul; Wahyuni, Agus; Ali, Ruslan Mat (Universitas Syiah Kuala, 2025)
The limited integration of technology and innovative approaches in physics education has frequently hindered students' ability to comprehend abstract and complex concepts, contributing to suboptimal learning outcomes. This study investigates the impact of google sites-based physics instructional media, implemented in conjunction with a problem based learning model, on the learning outcomes of class XI students at SMAN 1 Darul Imarah, explicitly focusing on momentum and impulse topics. This research employs a quantitative approach using a quasi-experimental methodology with a nonequivalent control group design. The entire cohort of class XI students served as the population, with purposive sampling used to select class XI F-4 as the experimental group and XI F-5 as the control group. Data collection was performed through pretests and posttests, utilizing 20 multiple-choice questions designed to assess student comprehension. Data analysis was conducted using an independent sample t-test to determine the significance of differences between groups. The analysis revealed that a t-value (count) of 2.205 exceeded the critical t-value (table) of 1.996, indicating a statistically significant difference in learning outcomes associated with google sites-based physics instructional media using the probkem based learning model with respect to learning outcomes. These findings demonstrate that the integration of google sites as an instructional medium, coupled with the problem based learning approach, significantly enhances students' learning outcomes in the study of momentum and impulse.